Role of Exercise in Developing Scientific Methodology for Future Classroom Teachers (An example of a course in Natural Science and Teaching Methodology) - Hudoykulova Shahlo Mamaniyozovna (International Consortium of Education and Culture Research Studies, 2019)
The skills of the teaching staff in organizing and conducting the training play an important role in the preparation of future elementary teachers. The teacher takes into account the didactic purpose of the study subject, which is derived from the course program of Natural Science and Teaching Methodology